TINJAUAN KEPUASAN PASIEN RAWAT INAP DALAM MELAKUKAN PEMBAYARAN (BILLING SYSTEM) DI RSUD dr. RASIDIN PADANG TAHUN 2018 - Oktamianiza Oktamianiza; Legita Nadia Rahmi (Ensiklopedia of Journal, 2019)
Satisfaction is the first indicator of a hospital's standard for measuring service quality. The results of the observations found that there were patient or family dissatisfaction caused by the long awaiting the payment process (billing system) carried out by the officer manually with the RSUD dr. Rasidin Padang. Therefore the researcher was interested in conducting a research on Patient Satisfaction in Making Payment (Billing System) in RSUD Dr.Rasidin Padang in 2018. The type of research was descriptive. This research was conducted at the RSUD dr. Rasidin Padang. The population in this study were all inpatients who received payment services, with a total sample of 62 with accidental sampling technique. Data collection is done by interviewing inpatients who are in the process of paying health service fees. Based on the results of the study, more than half (54.8%) of respondents were not satisfied in making payments, more than half (67.7%) of respondents who said the waiting time in payment was longer, and more than half (56.5%) of respondents said that the lack of technical competence of the staff in processing the payment of patient care costs at the RSUD dr. Rasidin Padang. The patient's dissatisfaction in paying for inpatient health services is more due to the payment system that is still done manually, resulting in difficulties in collecting and calculating total payments for health services and making it difficult for patients / families to process payments. The researcher suggested that the hospital make an SOP about the payment system as a guideline or guideline in carrying out its work, implement a payment system that has been integrated with other systems and suggest that officers fill in the complete and exact data needed in the process of paying patient care costs.